THE PRINCIPLES OF CASHLESS SETTLEMENTS ARE ALSO THE PRINCIPLES OF PAYMENT CIRCULATION (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
In organizing this or that thing or solving existing problems, the principles scientifically based on its basis are of great importance. If the principles are scientifically based and set correctly, most of the problems that may arise in the system are determined by the violation of these principles. Therefore, in order to solve the problem that has arisen, first of all, it is necessary to achieve full compliance with the principles accepted as the basis. Otherwise, it will not be possible to solve the problem and it will deepen. These points are fully applicable to all economic processes, including payment circulation.